Ameliorative Effects of Curcumin on Artesunate-Induced Subchronic Toxicity in Testis of Swiss Albino Male Mice. Issue 2 (26th June 2015) - Desai, Ketaki R.; Rajput, Dhrupadsinh K.; Patel, Pragnesh B.; Highland, Hyacinth N.
India is one of the endemic areas where control of malaria has become a formidable task. Artesunate is the current antimalarial drug used to treat malaria, especially chloroquine resistant. The objective of the present study was to investigate the dose-dependent effect of oral administration of artesunate on the oxidative parameters in testes of adult male Swiss albino mice and ameliorative efficacy of curcumin, a widely used antioxidant. An oral dose of 150 mg/kg body weight (bwt; low dose) and 300 mg/kg bwt (high dose) of artesunate was administered for a period of 45 days to male mice, and ameliorative efficacy of curcumin was also assessed. The results revealed that artesunate caused significant alteration in oxidative parameters in dose-dependent manner. Administration of artesunate brought about significant decrease in activities of superoxide dismutase, glutathione, glutathione peroxidase, and glutathione reductase, whereas lipid peroxidation and glutathione-S-transferase activity were found to be significantly increased. The results obtained show that oxidative insult is incurred upon the intracellular antioxidant system of testis tissue by artesunate treatment. Further, administration of curcumin at the dose level of 80 mg/kg bwt along with both doses of artesunate attenuated adverse effects in male mice.